2022
DOI: 10.1128/jvi.01724-21
|View full text |Cite
|
Sign up to set email alerts
|

Noncognate Signals Drive Enhanced Effector CD8 + T Cell Responses through an IFNAR1-Dependent Pathway after Infection with the Prototypic Vaccine, 0ΔNLS, against Herpes Simplex Virus 1

Abstract: Previous studies by our group identified a highly efficacious vaccine 0ΔNLS (deficient in the nuclear localization signal of infected cell protein 0) against HSV-1 in an experimental ocular mouse model. However, details regarding fundamental differences in the initial innate and adaptive host immune response were not explored. Here, we present a side-by-side analysis of the primary infection characterizing differences of the host immune response in mice infected with 0ΔNLS versus the parental, GFP105. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Previously, we reported 0∆NLS-vaccinated mice displayed more functional HSV-1 gB-specific CD8 + T cells 7 days post-vaccination compared to mice immunized with GFP105 38 . Similar to the experimental design above, we wished to determine whether this relationship held following the booster immunization, mice vaccinated with GFP105 or 0∆NLS were evaluated for IFN-γ-secreting, HSV-1 gB-specific CD8 + T cells at 21 days post-primary immunization and 30 days post-boost.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…Previously, we reported 0∆NLS-vaccinated mice displayed more functional HSV-1 gB-specific CD8 + T cells 7 days post-vaccination compared to mice immunized with GFP105 38 . Similar to the experimental design above, we wished to determine whether this relationship held following the booster immunization, mice vaccinated with GFP105 or 0∆NLS were evaluated for IFN-γ-secreting, HSV-1 gB-specific CD8 + T cells at 21 days post-primary immunization and 30 days post-boost.…”
Section: Resultsmentioning
confidence: 81%
“…Still, another cytokine IL-12, has been shown to promote differentiation of naive B cells into plasma cells 60 . In a previous study, we reported following initial vaccination with HSV-1 0∆NLS, an elevation in type I IFN and IL-12 production by cells was noted which drove an increase in IFN-γ-expressing CD8 + T cells in comparison to mice vaccinated with GFP105 38 . Thus, using the same vaccination model, changes in B cell subset formation may be linked to an altered cytokine microenvironment.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations